Liquid rocket combustion chamber acoustic characterization - Cândido Magno de Souza; Luiz Carlos Sandoval Góes; Dimas Donizeti da Silveira; Rogério Pirk; Carlos d’Andrade Souto (Journal of Aerospace Technology and Management, 2010)
Over the last 40 years, many solid and liquid rocket motors have experienced combustion instabilities. Among other causes, there is the interaction of acoustic modes with the combustion and/or fluid dynamic processes inside the combustion chamber. Studies have been showing that, even if less than 1% of the available energy is diverted to an acoustic mode, combustion instability can be generated. On one hand, this instability can lead to ballistic pressure changes, couple with other propulsion systems such as guidance or thrust vector control, and in the worst case, cause motor structural failure. In this case, measures, applying acoustic techniques, must be taken to correct/minimize these influences on the combustion. The combustion chamber acoustic behavior in operating conditions can be estimated by considering its behavior in room conditions. In this way, acoustic tests can be easily performed, thus identifying the cavity modes. This paper describes the procedures to characterize the acoustic behavior in the inner cavity of four different configurations of a combustion chamber. Simple analytical models are used to calculate the acoustic resonance frequencies and these results are compared with acoustic natural frequencies measured at room conditions. Some comments about the measurement procedures are done, as well as the next steps for the continuity of this research. The analytical and experimental procedures results showed good agreement. However, limitations on high frequency band as well as in the identification of specific kinds of modes indicate that numerical methods able to model the real cavity geometry and an acoustic experimental modal analysis may be necessary for a more complete analysis. Future works shall also consider the presence of passive acoustic devices such as baffles and resonators capable of introducing damping and avoiding or limiting acoustic instabilities.